The Effect Of Using The Flipped Classroom Learning Model Using Video Interactive Media On Learning Outcomes - Mispandi Mispandi; Muh. Fahrurrozi; Siti Mawaddah (IJE : Interdisciplinary Journal of Education, 2023)
This study aims to determine the effect of using the flipped classroom learning model using video interactive media on the learning outcomes of class X IPS students in economics at SMAN 1 Suela. The type of research used is experimental research. The population in this study were all students of class X IPS. Which consists of class X IPS A, X IPS B, X IPS C. Random sampling technique (random sampling technique). The instrument used is an objective test in the form of multiple choice consisting of 25 questions. Data analysis used data normality test, data homogeneity test, and hypothesis testing used parametric statistical tests. The results of the experimental class research showed that the highest score was 95 and the lowest score was 76 with a post-test average of 82.03 and a standard deviation of 5.245. Whereas in the control class the highest score was 90 and the lowest score was 60 with an average post-test score of 76.13 and a standard deviation of 7.074. For the results of hypothesis testing for learning outcomes for the experimental class and control class obtained a significance value (2- tailend) on the t-test for Equality of Means of 0.000 <0.05 meaning that Ho is rejected and Ha is accepted. This means that the use of the Flipped Classroom Learning Model Using Video Interactive Media Has a Positive and Significant Influence on the Learning Outcomes of Class X IPS Students in the Subject of Economics at SMAN 1 Suela Tahuan Lesson 2022.